Restoration of the Vertical Posterior Dimension in a Grinding Patient before Orthodontic Treatment: A Case-Report with Electromyographic Evaluation of Masticatory Muscles Balance - Edoardo, Bianco; Sara, Attuati; Cristina, Brugali; Alessandro, Nanussi; Marcello, Maddalone (The Journal of Dentists, 2019)
Aim: the aim of this article is to assess the importance of masticatory muscles balance evaluation before improving vertical dimension through conservative and restorative techniques. It also shows how a multidisciplinary approach is needed to obtain a better result for the patient. Background: Bruxism is defined as the parafunctional activity of grinding or clenching of teeth. Management of severe worn dentition in patients with bruxism is challenging since this condition can lead to loss of tooth structure and occlusal vertical dimension (OVD). In some cases the impossibility to correct the proclination of the maxillary incisors occurs due to the posterior tooth wear. Case Description: an orthodontic alignment was obtained after having improved posterior vertical dimension according to an electromyographical analysis using Teethan® electromyographic system. The activity of anterior temporals and masseters was controlled and balanced by electromyography at every step of the treatment. Conclusion: an unbalanced dental occlusal function can compromise the stability of an orthodontic treatment; it is important an evaluation from different points of view in order to rehabilitate the patient in his complex. Clinical significance: electromyography proved itself to be a useful tool in the hands of the clinician to check the oral muscles balance and to avoid temporomandibular joint (TMJ) overload in restorative dentistry, prosthodontics and orthodontics.